2008
DOI: 10.1080/02640410801885958
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates of cardiorespiratory fitness and muscle strength in overweight and obese post-menopausal women: A MONET study

Abstract: The purpose of this study was to examine the psychosocial correlates of cardiorespiratory fitness (VO2peak) and muscle strength in overweight and obese sedentary post-menopausal women. The study population consisted of 137 non-diabetic, sedentary overweight and obese post-menopausal women (mean age 57.7 years, s = 4.8; body mass index 32.4 kg.m(-2), s = 4.6). At baseline we measured: (1) body composition using dual-energy X-ray absorptiometry; (2) visceral fat using computed tomography; (3) insulin sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…After reading and signing the consent form, each participant was invited to the Metabolic Unit for a series of tests. Inclusion criteria and methods for body composition, computed tomography, blood pressure, blood samples, OGTT, cardiorespiratory fitness (VO 2 peak ), energy expenditure, and insulin sensitivity were determined as previously described (25,26,27,28). Briefly, women were included in the study if they met the following criteria: (i) BMI between 30 and 40 kg/m 2 , (ii) cessation of menstruation for >1 year and a follicle‐stimulating hormone level ≥30 U/l, and (iii) free of known inflammatory disease.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…After reading and signing the consent form, each participant was invited to the Metabolic Unit for a series of tests. Inclusion criteria and methods for body composition, computed tomography, blood pressure, blood samples, OGTT, cardiorespiratory fitness (VO 2 peak ), energy expenditure, and insulin sensitivity were determined as previously described (25,26,27,28). Briefly, women were included in the study if they met the following criteria: (i) BMI between 30 and 40 kg/m 2 , (ii) cessation of menstruation for >1 year and a follicle‐stimulating hormone level ≥30 U/l, and (iii) free of known inflammatory disease.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Although some investigators have reported improvements in quality of life with resistance training (Rejeski et al, 2002), others have not (Perrig-Chiello, Perrig, Ehrsam, Staehelin, & Krings, 1998). Thus, this area of study needs to be addressed because: (1) there are limited and contradictory data on the effect of resistance training combined with caloric restriction on individuals' psychosocial profile; (2) resistance training-strength activities are part of current physical activity recommendations (Haskell et al, 2007); and (3) psychosocial correlates may differ for cardiorespiratory fitness, as related to aerobic activities, compared with muscle strength, as related to resistance training (Karelis et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…31 The SF-36 and Medical Outcomes Study General Health Survey (MOS) questionnaires, which are derived from the same study, were the most prevalent generic tools, being found in eight articles. 23,25,26,[28][29][30][31][32] The SF-36 was the most widely adopted, being found in six articles, 23,25,26,[30][31][32] which is consistent with the literature, since it is the most widely used generic instrument documented in over four hundred publications. 40,41 However, none of these questionnaires takes into consideration important aspects such as menopausal symptoms or specific psychosocial conditions regarding this time of life, which hinders the assessment of quality of life in this population.…”
Section: Discussionmentioning
confidence: 50%
“…Six articles used generic instruments combined with psychosocial questionnaires, showing that the use of generic instruments may fail to take into account important aspects of quality of life in the period close to menopause. 23,25,27,29,31,32 Ashok et al 22 used the World Health Organization five-item well-being index (WHO-5) well-being questionnaire, which assesses psychological and not physical dimensions related to menopause. 22 Lynch et al 25 used the SF-36 together with a questionnaire to determine psychosocial quality of life created from instruments used in the life circumstances, should be included; i.e., occupational, sexual, emotional and health-related factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation